2001
DOI: 10.1021/jp0112065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reverse Micelle Size on the Librational Band of Confined Water and Methanol

Abstract: We report measurement of the OH librational band in nanoscopic pools of water and methanol confined within reverse micelles. The librational band, which peaks near 670 cm-1 in the bulk liquids, shifts to lower frequency as the reverse micelle size decreases. In addition, the shape of the band changes considerably as a function of decreasing size. The librational band at all compositions is well fit by a two-state model based on the relative fractions of bound and free water (or methanol) within the reverse mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
215
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(231 citation statements)
references
References 35 publications
12
215
1
2
Order By: Relevance
“…The red shift of the OH librational band with decreasing reverse micelle size has also been attributed to a weaker hydrogen-bond network. 38 However, unlike bulk water, reverse micelles have interfacial waters at the headgroup layer. As the size of the reverse micelle is reduced, the relative number of these interfacial waters increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The red shift of the OH librational band with decreasing reverse micelle size has also been attributed to a weaker hydrogen-bond network. 38 However, unlike bulk water, reverse micelles have interfacial waters at the headgroup layer. As the size of the reverse micelle is reduced, the relative number of these interfacial waters increases.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 The existence of an isosbestic point in the reverse micelle sizedependent FTIR spectra of the librational band of water (∼600 cm -1 ) suggests the possibility of two types of water, although the line shapes contain a good deal of inherent structure, particularly for the smallest reverse micelles. 38 From the absorption spectra displayed in Figure 1, it is impossible to decompose the spectra into several contributions arising from different "types" of water. The OD stretch of an HOD molecule is a local mode, and there is no Fermi resonance.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the dimension, shape, and overall charge of reverse micelles can be conveniently modulated which make them particularly useful for monitoring the dynamics of confined liquids. The properties of water in reverse micelles of AOT at low w o values are rather different from those of bulk water (Jain et al, 1989;Ikushima et al, 1997;Brubach et al, 2001;Venables et al, 2001). Even at higher water content (w o 0/50), the apparent microviscosity is 6Á/9 times greater than that of free aqueous solutions (Andrade et al, 2000).…”
Section: Wavelength-selective Fluorescence In Reverse Micellesmentioning
confidence: 96%
“…The physical and chemical properties of the entrapped water are markedly different from the properties of bulk water but similar in several aspects to those of biological interfacial water as found in membrane or protein interfaces. Both experimental (Jain et al, 1989;Ikushima et al, 1997;Brubach et al, 2001;Venables et al, 2001) and theoretical approaches (Faeder and Ladanyi, 2000) have shown that the crucial structural parameter of reverse micelles is the (water/surfactant) molar ratio (w o ) which determines their size as well as the extent of deviation of the properties of the entrapped water from those of normal bulk water. Reverse micelles thus represent a type of organized molecular assembly which offer the unique advantage of monitoring dynamics of molecules with varying degrees of hydration.…”
Section: Wavelength-selective Fluorescence In Reverse Micellesmentioning
confidence: 99%
“…To manipulate still ultrasmaller volumes of liquids in such diverse fields as cell biology, microfluidics, capillary chromatography, and nanolithography, one needs a better understanding of fluid behavior confined in attoliter volume. [1][2][3][4][5][6][7] Indeed, water in nanometer-sized restricted geometries, such as micelles and microemulsions, 8,9 nanometer films, 10,11 and nanoporous silica, 12 often shows different and sometimes unexpected features in comparison to bulk water. The trend of miniaturization in conventional microchip devices consisting of poly(dimethylsiloxane), silicone, and glass has thus directed growing attention to new femtoliter (fL ¼ 10 À15 L) or attoliter (aL ¼ 10 À18 L) vessels like carbon 13 and silica nanotubes.…”
Section: Introductionmentioning
confidence: 99%